The Role of Instagram in Shaping Spiritual Resilience and Identity among Undergraduate Generation Z - Hariyati, Farida; Pranawati, Rita (Jurnal The Messenger, 2025)
Purpose: This study investigates how undergraduate students Generation Z, who are immersed in digital and urban environments, develop spiritual resilience through their communicative practices on social media, particularly Instagram. It aims to elucidate the dynamic interplay between spirituality, self-control, and the formation of digital identity a central factors in cultivating resilience.   Methods: Employing a qualitative case-study approach, this research conducted in-depth interviews with eight Gen-Z students in Jakarta. As members of an urban society and active digital users, these participants represent information-rich cases that provide deep insights into lived experiences rather than generalizable findings.   Findings: The findings reveal that social media functions both as a source of spiritual motivation and a trigger of internal conflict. Participants used Instagram for self-expression, information seeking, and spiritual encouragement beyond recreational purposes. Key indicators of spiritual resilience emerged, including self-control, time management, negotiation of multiple identities, and intentional digital detox practices. The students demonstrated critical awareness of social media’s dual impact and actively balanced digital engagement with academic, spiritual, and emotional responsibilities.   Originality: This study offers a novel integrated approach by synthesizing digital nativity, spiritual purpose, and adaptive resilience, which are often examined separately. It bridges the gap in existing literature by exploring the nexus of Gen-Z’s unique digital communication on Instagram and their search for spiritual meaning. By examining these converging dimensions, the research provides a holistic understanding of how communicative processes function as tools for navigating modern adversities.